2015
DOI: 10.3389/fmicb.2015.00999
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of combination therapy in BALB/c mice injected with carbapenem-resistant Enterobacteriaceae strains

Abstract: Monotherapeutic options for carbapenem resistant infections are limited. Studies suggest that combination therapy may be associated with better outcomes than monotherapies. However, this is still controversial. This study assessed, the efficacy of combination therapy against carbapenem resistant Enterobacteriaceae harboring singly various extended spectrum beta lactamase or carbapenemase encoding genes. Thus, four isolates harboring either blaCTXM-15, blaCTXM-15 and blaOXA-48, blaNDM-1, or blaKPC-2 genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Studies at our medical center since 2008 have been addressing molecular characterizations, resistance mechanisms, genes involved, and other aspects of CR Ec and Kp isolates [9,10,[12][13][14]. The first CRE detected in Lebanon was a K. pneumoniae recovered from a 7year-old female child, which was characterized by PCR experiments using primers for multiple β-lactamase and carbapenemase genes: TEM, SHV, CTX-M, GES, KPC, IMI, OXA-1 ⁄ 2 ⁄ OXA-10 ⁄ 18, OXA-23 ⁄ 58, IMP, VIM, SPM, GIM and SIM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies at our medical center since 2008 have been addressing molecular characterizations, resistance mechanisms, genes involved, and other aspects of CR Ec and Kp isolates [9,10,[12][13][14]. The first CRE detected in Lebanon was a K. pneumoniae recovered from a 7year-old female child, which was characterized by PCR experiments using primers for multiple β-lactamase and carbapenemase genes: TEM, SHV, CTX-M, GES, KPC, IMI, OXA-1 ⁄ 2 ⁄ OXA-10 ⁄ 18, OXA-23 ⁄ 58, IMP, VIM, SPM, GIM and SIM.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the effects of antimicrobial combination therapy against bacteria with different CR genes using BALB/c mice [13]. The mice were injected with carbapenem-resistant Enterobacteriaceae strains, harboring either bla CTXM-15 , bla CTXM-15 and bla OXA-48 , bla NDM-1 , or bla KPC-2 genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We wanted to test whether we can use optical diagnostic imaging to monitor the efficacy of current and novel therapeutics noninvasively, and since we have demonstrated that the JSKP001 strain is sensitive to meropenem, we decided to utilize this antibiotic as a proof of concept to investigate this question. Meropenem is an important drug for treating K. pneumoniae infections including pneumonia [43,87,118,[265][266][267]. Therefore, we decided to investigate if meropenem is capable of resolving the respiratory disease and if the direct impact of the therapeutic on bacterial viability can be monitored in vivo using BLI.…”
Section: Noninvasive Monitoring Of Meropenem Therapeutic Efficacy In mentioning
confidence: 99%